Baclofen Withdrawal - Elaine Fielder; Daniel Lemke; Cara Doughty (Association of American Medical Colleges, 2014)
Abstract This case centers on an adolescent patient with altered mental status, agitation, and suspected intrathecal baclofen (ITB) pump failure. Learners should recognize and appropriately manage suspected baclofen withdrawal, manage agitation and spasticity, demonstrate appropriate airway and circulatory management, appropriately consult subspecialists (including physical medicine and rehabilitation and/or neurosurgery), and provide patient disposition to a pediatric critical care unit. At least two simulation faculty and two personnel members per scenario are required for a successful simulation experience. Participants were informed that this was a non-graded interactive learning experience (similar to other simulation days they had previously experienced). They were informed that scenarios were chosen specifically to be challenging and that mistakes are both expected and welcomed as learning opportunities. This simulation case was piloted at the Texas Children's Hospital Simulation Center on July 21, 2012 with 12 pediatric emergency medicine fellows and four pediatric emergency medicine nurses. All participants filled out a course evaluation at the end of the simulation day, which included specific feedback about scenarios, content, and instructors. Based on this feedback, scenarios were modified in May 2013 and May 2014 for future use.